MECANISMUL FUNCTIONĂRII PARLAMENTULUI ROMÂNIEI - Piroşca, Alina (CEP USM, 2010)
This article represents a short description of the functioning mechanism of the Romanian Parliament. The functioning is based on the Constitution and some other regulations that are meant to consolidate democracy in Romania. Romania is a parliamentary republic, so the functioning in democratic lines of the Parliament has a great importance. The Parliament’s decisions can change the future in good or bad. In conclusion, a good and democratic representation is crucial.
Keywords: Parlamentul României; funcţionarea Parlamentului